2009
DOI: 10.3200/socp.149.3.402-408
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Procrastination Among Turkish Adults: Exploring Decisional, Avoidant, and Arousal Styles

Abstract: The authors examined the prevalence of chronic procrastination (decisional, avoidant, and arousal styles) as functions of demographic variables among 354 Turkish adults (148 men, 206 women; M age = 38.7 years, SD = 8.26 years). Prevalence analyses showed that among Turkish participants, 17.5% were indecisive procrastinators, 13.8% were avoidant procrastinators, and 14.7% were arousal procrastinators. Results did not yield significant differences for gender or age on any forms of procrastination, which is consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 4 publications
1
41
1
4
Order By: Relevance
“…This result may indicate that age does not play a significant role in academic procrastination. The current finding is consistent with earlier research conducted by Ferrari et al (2009) but in contrast with the findings of several other studies. Steel (2007) found a negative relationship between procrastination and age, hypothesising that people should expect to have fewer tendencies to procrastinate as they age and learn.…”
Section: Discussioncontrasting
confidence: 56%
“…This result may indicate that age does not play a significant role in academic procrastination. The current finding is consistent with earlier research conducted by Ferrari et al (2009) but in contrast with the findings of several other studies. Steel (2007) found a negative relationship between procrastination and age, hypothesising that people should expect to have fewer tendencies to procrastinate as they age and learn.…”
Section: Discussioncontrasting
confidence: 56%
“…Epidemiological studies establish that self-reported procrastination is present in at least 20% of the general adult population [ 2 ], and that chronic procrastination is common among English-speaking countries (i.e., Australia, United Kingdom, and United States) and Spanish-speaking countries (i.e., Peru, Spain, and Venezuela) where around 14% of adults self-identified as procrastinators [ 3 ]. In a Turkish sample, prevalence analysis revealed 15% of the adult population to be chronic procrastinators [ 4 ]. These studies used self-reported measures of procrastination, leaving out of their scope to what extent chronic procrastinators present a clinical condition that warrants intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of procrastination in older adults was studied from different angels (Ferrari et al, 2007 ; Tibbett and Ferrari, 2015 ). Epidemiological studies in English speaking countries, in Germany, Turkey, and six Spanish talking countries indicated that people procrastinate less as they age, when they are educated, married, have a job and reside in countries with higher levels of self-discipline (Ferrari et al, 2005b , 2007 , 2009b ; Gröpel and Steel, 2008 ; Steel and Ferrari, 2013 ; Beutel et al, 2016 ). Further, it was revealed that procrastination in older adults is associated with emotional variables such as life regrets (Ferrari et al, 2009a ), perceived stress, distress (depression, anxiety, fatigue), and reduced life satisfaction across a broad set of life-domains (Beutel et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%